Formation of the Outer Radiation Belt: Adiabatic Effect and Stochastic Acceleration - Espinoza-Romo, C; Stepanova, M; Pinto-Abarzua, V (Springer Nature, 2023)
In this work, we discuss the problems associated with the formation of the outer radiation belt (ORB) taking into account previous results, including the recent ones. In our opinion, the traditional approaches to the dynamics of the ORB have the following problems: • inconsistency between the times provided by the popular “quasilinear” approach to the ORB description and the observed electron acceleration times; • impossibility to describe ORB dynamics during magnetospheric storms using the “quasilinear” approach when the particle fluxes after storm restore to their pre-storm values, i.e., belong to the storms of the third type according to Reeves et al. (2003, https://doi.org/10.1029/2002GL016513) classification; • impossibility of explaining the Tverskaya’s relation, which connects the position of the maximum of the relativistic flux formed after storm with the minimum value of the Dst/SYM-H variation, as well as the acceleration of relativistic electrons during magnetospheric substorms even in the absence of storms. We show that such difficulties do not appear if we take into account the large-scale magnetospheric dynamics, including auroral oval shift toward low latitudes during storms, substorm injections into the region of depressed magnetic field during storm recovery phase and the action of the adiabatic mechanism of electron deceleration and acceleration. The action of stochastic mechanisms of ORB acceleration is also discussed. © 2023, Springer Nature. All rights reserved.